Solutions of Neumann Boundary Value Problems for Higher Order Nonlinear Functional Difference Equations With p-Laplacian - Liu, Yuji (Sarajevo Journal of Mathematics, 2024)
Sufficient conditions for the existence of at least one solution of Neumann boundary value problems for higher order nonlinear functional difference equations with p-Laplacian are established. We allow f to be at most linear, superlinear or sublinear in the obtained results. 2000 Mathematics Subject Classification. 34B10, 34B15